Inoculation with arbuscular mycorrhizal fungus modulates defense-related genes expression in banana seedlings susceptible to wilt disease. (4th May 2021) - Lin, Ping; Zhang, Minyu; Wang, Mingyuan; Li, Yuqing; Liu, Jianfu; Chen, Yinglong
ABSTRACT: Banana as an important economic crop worldwide, often suffers from serious damage caused by Fusarium oxysporum f. sp. Cubense . Arbuscular mycorrhizal (AM) fungi have been considered as one of the promising plant biocontrol agents in preventing from root pathogens. This study examined the effect of AM fungal inoculation on plant growth and differential expressions of growth- and defense-related genes in banana seedlings. Tissue-cultured seedlings of Brazilian banana ( Musa acuminate Cavendish cv. Brail) were inoculated with AM fungus ( Rhizophagus irregularis, Ri), and developed good mycorrhizal symbiosis from 4 to 11 weeks after inoculation with an infection rate up to 71.7% of the roots system. Microbial abundance revealed that Ri abundance in banana roots was 1.85×10 6 copies/ml at 11 weeks after inoculaiton. Inoculation improved plant dry weights by 47.5, 124, and 129% for stem, leaf, and the whole plant, respectively, during phosphate depletion. Among a total of 1411 differentially expressed genes (DEGs) obtained from the transcriptome data analysis, genes related to plant resistance (e.g. POD, PAL, PYR, and HBP-1b) and those related to plant growth (e.g. IAA, GH3, SAUR, and ARR8) were up-regulated in AM plants. This study demonstrates that AM fungus effectively promoted the growth of banana plants and induced defense-related genes which could help suppress wilt disease. The outcomes of this study form a basis for further study on the mechanism of banana disease resistance induced by AM fungi.